THE EFFECT OF LIGHT INTENSITY ON PLANT GROWTH AND YIELD - Hina Ashraf Bhat; Mohammad shah Aadil Mir (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Light intensity plays a pivotal role in determining the growth and yield of plants by influencing their physiological processes, particularly photosynthesis. This paper reviews current research on how varying light intensities affect plant development, biomass production, and crop yield. Studies consistently show that optimal light conditions enhance photosynthetic efficiency and overall productivity, while inadequate or excessive light can lead to physiological stress and reduced yields. Understanding these relationships is crucial for optimizing agricultural practices, particularly in controlled environments like greenhouses. By manipulating light intensity effectively, farmers can maximize crop yields, ensure food security, and promote sustainable agriculture in diverse environmental conditions.